2020
DOI: 10.3390/molecules25173871
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of β-Lactoglobulin and Gum Arabic Complexes: the Role of pH

Abstract: Protein–polysaccharide complexes have received increasing attention as delivery systems to improve the stability and bioavailability of multiple bioactive compounds. However, deep and comprehensive understanding of the interactions between proteins and polysaccharides is still required for enhancing their loading efficiency and facilitating targeted delivery. In this study, we fabricated a type of protein–polysaccharide complexes using food-grade materials of β-lactoglobulin (β-Lg) and gum arabic (GA). The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…In recent years, GA has been combined to a variety of proteins, such as milk, egg, wheat, rice, and soybean proteins (Li et al., 2019; Niu et al., 2017; Wei & Huang, 2019). The latest research showed that the electrostatic interactions were the main driven force for the formation of the β‐Lg‐GA nanoparticles (Wang et al., 2020). Schmitt et al (2000) studied the effect of protein aggregates on the complex coacervation between β‐Lg and GA at pH 4.2, which showed that the pH can affect β‐Lg aggregation and thus the formation of β‐Lg‐GA nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, GA has been combined to a variety of proteins, such as milk, egg, wheat, rice, and soybean proteins (Li et al., 2019; Niu et al., 2017; Wei & Huang, 2019). The latest research showed that the electrostatic interactions were the main driven force for the formation of the β‐Lg‐GA nanoparticles (Wang et al., 2020). Schmitt et al (2000) studied the effect of protein aggregates on the complex coacervation between β‐Lg and GA at pH 4.2, which showed that the pH can affect β‐Lg aggregation and thus the formation of β‐Lg‐GA nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The above typical peaks indicated the presence of a large fraction of protein [ 32 ]. GA is a heteropolysaccharide that consists of galactose and glycoproteins [ 33 ]. The FTIR spectrum of GA showed a broad peak at 3389 cm −1 , which was attributed to the amino groups (Amide A).…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectrum of GA showed a broad peak at 3389 cm −1 , which was attributed to the amino groups (Amide A). The peaks at 1606 cm −1 and 1420 cm −1 corresponded to the asymmetrical and symmetrical stretching vibrations of –COOH groups with the negative charge [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Near the isoelectric point (pI = 5.1), it, however, starts to aggregates and form a different structure depending on the ionic strength and pH of the solution [ 7 ]. There is a possibility to impress the aggregation, thereby generating functional properties of Blg when it enters complexation with other biopolymers such as acacia gum [ 8 ], pectin [ 9 ], and κ-carrageenan [ 10 ].…”
Section: Introductionmentioning
confidence: 99%